Analisis Strategi Pengembangan Pemasaran Berbasis Pasar dalam Upaya Meningkatkan Kinerja Pemasaran Bank Sampah - Sri Sukartono; Eddy Jusuf; Juanim Juanim (Jurnal Syntax Admiration, 2023)
The waste problem is a common phenomenon in many countries. Uncontrolled waste accumulation can damage the beauty of the city, disrupt public health, cause disasters such as floods, water pollution, air pollution and so on. Various models of waste management have been carried out by several parties to reduce waste problems, one of which is through the Garbage Bank. This research was conducted at the Bersinar Waste Bank, Bandung and was qualitative in nature using the Exploratory Research method and Snowball Sampling interview method with the leadership, employees and customers of the Bersinar Waste Bank, as key informants. Using the 7P Marketing Strategy concept (Product, Price, Place, Promotion, People, Process, Physical Evidence) with marketing planning using STP (Segmenting, Targeting, Positioning) by Philip Kotler and Keller (2016) and making a SWOT analysis to choose the implementation of performance strategies proper marketing. The results of the research show that the strengths and weaknesses as well as external factors containing opportunities and threats in terms of management aspects and marketing aspects can be known precisely, what strategies will be taken in the marketing process and performance to increase the number of customers and sales volume at Bank Sampah Bersinar using the SWOT Matrix. Companies design policies based on weakness-opportunity (WO) strategy, strength-opportunity (SO) strategy, strength-threat (ST) strategy and weakness-threat (WT) strategy. Providing intensive counseling to customers, in sorting waste so that it has high value, taking advantage of opportunities and overcoming existing threats such as the need to recruit all scavengers around the waste bank to become customers at the Bersinar Waste Bank.